Diversi Penyidik Sebagai Bentuk Penyelesaian Perkara Pidana Anak Melalui Restorative Justice System : Studi Polrestabes Semarang - Andrean Widiyantoro; Sunarto Sunarto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The background to this thesis is that the implementation of diversion for children in the investigation process and legal processes related to juvenile criminal matters still faces significant gaps. Children's rights are often ignored in the implementation of diversion by the existing legal system. Disproportionate treatment of children in the implementation of diversion causes injustice in the handling of child criminal cases. There needs to be attention and effort to ensure that children's rights are fully recognized and respected in the implementation of diversion. Reforming the legal system to be more inclusive and attentive to children's needs is a necessary step to overcome this gap. The problem formulation for this thesis is: What is the process of investigating child criminal cases through restorative justice at the Semarang Police? and What are the obstacles and solutions in the process of investigating child criminal cases through restorative justice at the Semarang Police? The results of this thesis research are that the child diversion process at the Semarang Police is a method that involves transferring cases from the criminal court to a deliberative process, with the aim of achieving balance and restoring the situation. This approach has significant benefits, including reducing the number of children arrested, detained and sentenced to prison, as well as removing the stigma attached to them and returning them to normal behavior. In its implementation, deliberation involves a mediator who can be a trusted community figure or a school principal or teacher. The importance of a restorative judicial process is also seen in this case, involving law enforcement officials who have good intentions and understanding of children's problems. However, there are several obstacles in the child diversion process at the Semarang Police, such as excessive compensation requests, financial constraints, and the complexity of cases involving children. Apart from that, public trust in diversion regulations is also a concern that needs to be addressed.